Evaluating the Effectivity of the Audit Board’s Examination Report’s Follow-Up Recommendations Completion - Hendro Pratomo; Deddi Nordiawan (International Journal Labs, 2023)
This study discusses the effectiveness of following up BPK recommendations in Polewali Mandar District using the ISSAI 12 Value and Benefit framework by emphasizing stakeholder participation. This research uses a qualitative approach with a case study method. This study used interviews, observations, surveys, and documentation as instruments. Analysis of research data by analyzing primary and secondary data. The object of this research is Polewali Mandar Regency as the single entity being analyzed. The completion rate of follow-up on BPK recommendations by the Polewali Mandar Regency Government from 2016 to semester I of 2021 was the lowest among the six regencies in West Sulawesi Province. This study aims to determine the implementation and constraints in following up on BPK recommendations and provide solutions for their resolution. The principles used focus on exercising responsibility in response to audit findings and recommendations as well as effective communication with stakeholders. Identified follow-up settlement problems were findings of state losses related to civil servants and third parties whose whereabouts could no longer be known, administrative findings that were no longer relevant were followed up, lack of concern from SKPD and third parties in completing follow-up, and limited number of personnel in follow-up . Efforts to increase BPK's LHP follow-up so as to provide added value and benefits for the completion of BPK's LHP follow-up include setting priorities for completing follow-up, making commitments for completing follow-up, and increasing the capacity of follow-up team personnel.